Functional-level analysis of post-stroke social participation: A nationwide cohort study using the ICF framework - Jinhee Choi; Junhee Han; Hae In Lee; Min Kyun Sohn; Jongmin Lee; Deog Young Kim; Gyung Jae Oh; Yang-Soo Lee; Min Cheol Joo; So Young Lee; Min-Keun Song; Jeonghoon Ahn; et al. (PLoS ONE, 2026)
Background Social participation is a key goal in stroke rehabilitation, but its influencing factors vary by functional status. Few large-scale studies have categorized patients by functional level and analyzed associated factors using the International Classification of Functioning, Disability and Health (ICF) framework. Objective To identify determinants of social participation 12 months after stroke, stratified by functional level. Design and participants A cross-sectional analysis was conducted on 2,695 stroke survivors from a nationwide cohort in Korea. Participants were stratified into five groups based on Fugl-Meyer Assessment scores: Severe, Marked, Moderate, Slight, and Unimpaired. Methods Social participation was measured using the Reintegration to Normal Living Index. Independent variables were categorized into four ICF domains: personal factors, body functions and structures, activities and participation, and environmental factors. Multivariate regression analyses were performed by functional group. Results Predictors varied significantly across functional levels. In the Severe group (FMA < 50), environmental factors (home accessibility and caregiver-related variables such as age and relationship) were the primary determinants. Conversely, in higher-functioning groups (FMA ≥ 85), social participation was more strongly influenced by body functions and structures (cognitive, language, and psychosocial functions) and activities and participation factors (vocational status). Across all groups, activities and participation (functional independence and health-related quality of life) remained consistent positive predictors, while environmental barriers (caregiver burden) were universal constraints. Conclusion Determinants of social participation differ by functional status: individuals with lower functional levels are more significantly affected by environmental factors, whereas those with higher function face greater barriers related to body functions and structures. These findings suggest that stroke rehabilitation must provide functional-level-specific interventions, moving beyond physical recovery to address these distinct multidimensional barriers.